A Cognitive Study of Profiling in Vincent van Gogh 's (1889) The Starry Night (مجلة ديالى للبحوث الانسانية, 2022)
This study is an attempt to investigate the possibility of applying profiling parameter in Langacker's (2008 /2013) construal model to the visual domain represented by Van Gogh's (1889) canvas entitled The Starry Night. The study basically aims at finding out whether or not profiling can account for meaning construction in this type of texts. The study also aims at finding out the efficiency of the parameter to account for the reasons behind the variety of interpretations of this text by conceptualisers.     To achieve the aim of the study, two types of procedures have been followed: theoretical and practical. The theoretical part consists of presenting a brief theoretical framework of profiling parameter within the construal model of Langacker (2008 /2013). On the other hand, the practical part consists of analysing Van Gogh's (1889) “The Starry Night” by using the profiling parameter and its techniques.      The results of the study show that “profiling” can be applied to the visual domain.The results also show that canvases follow the same behaviour of linguistic entities since they have the same conceptual base, and both are part of the semiotic world. This means that they have the same content base and submit to the same coding process though they belong to different domains.